2001
DOI: 10.1038/sj.bmt.1702741
|View full text |Cite
|
Sign up to set email alerts
|

A three or more drug combination as effective therapy for moderate or severe chronic graft-versus-host disease

Abstract: Summary:We analyzed the results of a three or more drug combination as treatment for moderate or severe cGVHD developing after transplantation for thalassemia, in 45 patients with median age of 11 (range 2-26) years. Eighteen patients received a three drug regimen with cyclosporine (CsA), methylprednisolone (MP) and azathioprine (AZ) as first line therapy, 16 patients received this regimen as salvage therapy and 11 patients were given a four or five drug regimen with CsA, MP, AZ, cyclophosphamide (CY) and/or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Gaziev et al used three or more drugs in combination for the treatment of cGVHD. They found that patients receiving the three drug regimen as first line therapy had higher CR rates and fewer complications than did those receiving this combination as salvage treatment 12 while we found that MTX therapy effected a rapid response. GVHD-related symptoms in most patients improved within a few days and were controlled within 2-3 weeks after initiation of MTX.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…Gaziev et al used three or more drugs in combination for the treatment of cGVHD. They found that patients receiving the three drug regimen as first line therapy had higher CR rates and fewer complications than did those receiving this combination as salvage treatment 12 while we found that MTX therapy effected a rapid response. GVHD-related symptoms in most patients improved within a few days and were controlled within 2-3 weeks after initiation of MTX.…”
Section: Discussioncontrasting
confidence: 36%
“…To date, MTX has always been used as a single agent in the prevention of aGVHD after allo-HSCT, or as part of a combined regimen for treating cGVHD in both adult and pediatric patients. [10][11][12][13][14] There are no published data on the efficacy and the safety of low-dose MTX treatment in patients with acute or chronic GVHD.…”
mentioning
confidence: 99%
“…Notably, an overall clinical summary scale of mild, moderate, or severe chronic GvHD was the best predictor of survival based on Akaike's information criterion, a qualitative biostatistical method of comparing prognostic schemes (Lee et al , 2002a). However, formal definitions for the mild, moderate and severe categories have not been established (Gaziev et al , 2001).…”
Section: Classification Of Chronic Gvhdmentioning
confidence: 99%
“…The combination of the three drugs has fewer complications and lower mortality than the combination of multiple drugs. This retrospective study (Gaziev et al ., 2001) showed that the combination of three or more drugs is safe and effective for the treatment of moderate or severe cGVHD at least in younger patients. Therefore, we propose a method called IHRW to combine known potent drug combinations and unlabeled drug combinations for large-scale prediction of potential efficacious drug combinations.…”
Section: Introductionmentioning
confidence: 99%